Pembuatan Aplikasi Pemesanan Makanan Toko Manda Kitchen Berbasis Web - Ahmad Gernando Lisanto; Ahmad Rifky Fatah Al-Maliki; Dicky Firmanda Nurachman; Wasis Haryono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
At this time there are many shops engaged in the culinary field that still have shortcomings. Utilization of technology makes it possible to help humans to facilitate their work. One of the uses of technology in the culinary field is the Development of Web-Based Food Ordering Applications developed with the Prototyping system. In System Design using Unified Modeling Language, PHP Programming Language, Javascript and MySQL as its database. This writing will discuss how to make a web-based food ordering application which is of course to make it easier for Shop Owners and Consumers from Manda Kitchen Stores.